Residential relocation and travel behavior change: Investigating the effects of changes in the built environment, activity space dispersion, car and bike ownership, and travel attitudes - Ramezani, Samira; Hasanzadeh, Kamyar; Rinne, Tiina; Kajosaari, Anna; Kyttä, Marketta (Transportation research. Part A, Policy and practice, 2021)
•Reciprocal influences between travel attitudes, travel behavior, and car ownership.•Built environment modifies travel attitudes.•Characteristics of residential environment influence activity space dispersion.•Nudging approaches are effective in changing travel behavior. The influence of residential relocation, as a life event, on travel behavior has become the focus of research on determinants of travel behavior in recent years. Although several studies have investigated the influence of changes in the built environment of the residential environment, the complex relationships between the built environment, travel attitudes and travel behavior has remained controversial. One crucial research gap in this area is the paucity of longitudinal and semi-longitudinal research designs that could capture the influence of changes in the built environment, activity space dispersion, car and bike ownership, latent attitudes towards travel, as well as travel behavior, and the interrelationships between these factors. This study attempts to fill this gap by collecting retrospective travel behavior and attitudinal data in Helsinki Metropolitan Area using an online map-based survey tool. In total, 1321 residents who had relocated to a new residential location between three to eleven months prior to the survey date participated in the study. The study collected data related to common home-based trips during a typical week in September 2017 and September 2018, stated change in the use of different modes of transport after the move, as well as socio-demographic, and attitudinal data before and after the move. Based on residential location and the visited destinations during a typical week, respondents’ activity space dispersion was measured. Structural equation modelling was then used to investigate the interrelationships between changes in the built environment, activity space dispersion, car and bike ownership, travel attitudes, and travel behavior. Results indicate the existence of reciprocal influences between changes in car and bike ownership, travel attitudes, and travel behavior. It is also found that the built environment can modify and change travel related attitudes and influence activity space dispersion, which in turn affects travel behavior. The results of this study support the effectiveness of nudging approaches rather than marketing activities in changing travel attitudes and encouraging sustainable travel behavior.